REFUGEES : A HUMANITARIAN PROGRAM THAT IS BENEFICIAL FOR LONG TERM ECONOMIC DEVELOPMENT - Anita Herlina (Polteknik Imigrasi, 2022)
Refugees often portrayed in a negative light. However, Refugees are an asset for the host countries, in particular over longer term. This research explores to what extent refugees contribute an economic benefit for the hosts. In particular, this research’s specific research question is as follows: Do refugees harm or benefit host countries’ local jobs? This research uses a method of literature review. This research reviews the literatures to understand the key questions in the comprehension of host country benefits. It argues that refugees contribute an economic benefit for the receiving countries and do not harm the local jobs of the host countries. The findings in the research are as follows: first, the specific benefits refugees offer for the longer-term economic development of the host countries. Second, most of the refugees work in low-skilled jobs and do not harm local people’s jobs. Conversely, refugees can assist low-skilled local workers lift their skills and work into a higher wage and occupation set. Third, politicians together with the media have the most significant role in shaping the public’s perspective towards refugees. Fourth, the proper approach of integration policy leads to empowerment of refugees. Access to employment is the most significant government input to benefit the national economy. Finally, refugees can be an asset rather than a burden in the longer term. This effect is particularly the case in the second and third generations.